Causes of time delay in construction Sarawak, Malaysia - Harrison Yan, Rolland Duat (2014)
The aim of this study was to determine the factor that causes project delays in construction industries around Sarawak, Malaysia. By determining this factor, the project delays can be overcomed by the related group. Through literature review, 90 factors which lead to the time delay in construction were identified from previous studies which were then clustered into three categories; contractor-related, consultant-related, owner-related. As a result, 14 factors were selected for contractor-related, 11 factors were selected for consultant-related and 14 factors were selected for owner-related. A questionnaire was then developed and distributed to the 12 construction companies in Sarawak. Prior to questionnaire distribution, interviews had also been conducted to understand in depth the causes of project delays. Using Mean Square and Standard deviation analysis method, the questionnaires were then analysed and each factor was ranked. From the data analysis, Inadequate owner finance and payment of completed work were top ranked for the contractor-related with a score of 4.07. For the consultant-related, slow inspection of completed work with a score 3.84 was ranked as the highest factor which contributed to project delays in construction field. Meanwhile, slow payment of completed work with a score 4.32 was the most highest factor which had contributed to delay in construction for owner-related group.